The Effect Of Stocking Density and Feeding Rate On Growth and Survival Rate Of Gabus Larvae (Channa striata) - Putri Maya Fitri; Netti Aryani; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe aim of this research was to determine the effect of stocking density and feeding rate on growth and survival rate of common snakehead larvae. This research was conducted from Februari-April 2020 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The Method used was a Factorial Completely Randomized Design with two factors, the first was stocking density with three levels namely 3 larvae/L (S3), 5 larvae/L (S5) and 7 larvae/L (S7). While the second factor was feeding rate 60% (F60) and 80% (F80) of biomass. To minimize errors, each level of treatment was repeated 3 times. The result showed that stocking density and feeding rate were significant on absolute weight, absolute length, and survival rate. The treatment S3F80 (3 larvae/L and feeding rate 80% of biomass weight) were significant (P<0,05) with an absolute weight of 0,97 g, absolute length 4,80 cm, and survival rate 92,66 %. The water quality parameters during research was in optimal range temperature 26,5-26,9°C, pH 5,7-6 and dissolved oxygen 3,16-3,64 mg/l.Keywords : Stocking denstity, Feeding Rate, Growth and Survival rate